A high-flexibility polytetrafluoroethylene composite material and preparation method thereof

By adding modified bentonite, coconut fiber, pineapple leaf fiber and graphene to the polytetrafluoroethylene material, a stable network framework is formed, and the problem of insufficient flexibility of pure polytetrafluoroethylene material is solved through high-temperature sintering and cooling and cooling process, and a composite material with high flexibility and wear resistance is achieved.

CN119039722BActive Publication Date: 2025-02-28GUANGZHOU JINGBANG HYDRAULIC SEAL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411546205.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-28
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The softness of pure PTFE materials is insufficient, making it difficult to meet sealing applications that require high flexibility and good shape adaptability, which affects the tightness and durability of the seal.

Method used

Composite materials including modified bentonite, coconut fiber, pineapple leaf fiber and graphene are used to form a stable and elastic network framework through technical means such as microwave treatment and high-speed and low-speed alternating mixing, and further enhance the overall strength and softness of the material through high-temperature sintering and cooling cooling processes.

Benefits of technology

It significantly enhances the flexibility and wear resistance of the polytetrafluoroethylene composite material, improves the overall strength and stability of the material, and can better adapt to complex shapes and high load environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present application relates to a highly flexible polytetrafluoroethylene composite material and a preparation method thereof. A highly flexible polytetrafluoroethylene composite material comprises 1-20% modified bentonite, 5-10% coconut shell fiber, 5-10% pineapple leaf fiber, 1-5% graphene, and polytetrafluoroethylene; the preparation method thereof is as follows: preparing a mixture: mixing the mixture, modified bentonite, and polytetrafluoroethylene alternately at high speed and low speed at a temperature of 20-30°C to obtain an intermediate; molding the intermediate under the condition of 25-50MPa, and the holding time is 3-5min; sintering the molded intermediate under the condition of 220-370°C, and obtaining a highly flexible polytetrafluoroethylene composite material after cooling. The present application has the advantages of enhancing the softness and wear resistance of polytetrafluoroethylene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polytetrafluoroethylene composite materials, and more specifically, to a highly flexible polytetrafluoroethylene composite material and a preparation method thereof. Background Art

[0002] Polytetrafluoroethylene (PTFE), as a high-performance polymer material, has been widely used in the field of sealing materials due to its excellent chemical corrosion resistance, high temperature resistance and excellent electrical insulation properties. PTFE materials can still maintain stable performance in extreme environments, making it the preferred sealing material in a variety of industrial applications. However, despite the many advantages of PTFE, its lack of softness has limited its application range to a certain extent. Especially in those sealing applications that require materials to have high softness and good shape adaptability, pure PTFE materials are often difficult to meet the requirements.

[0003] Pure PTFE has high rigidity and relatively poor softness, which results in unsatisfactory performance of pure PTFE in sealing situations where the material needs to fit tightly to complex shapes or curved surfaces. The lack of softness not only affects the tightness of the seal, but may also reduce the durability and reliability of the seal. In addition, the mechanical strength and wear resistance of pure PTFE also have certain limitations, especially in high-load or high-friction working environments, the service life of pure PTFE seals may be seriously affected.

[0004] Therefore, there is room for improvement. Summary of the invention

[0005] In order to enhance the softness of polytetrafluoroethylene, the present application provides a polytetrafluoroethylene composite material with high softness and a preparation method thereof.

[0006] In the first aspect, the present application provides a highly flexible polytetrafluoroethylene composite material, which adopts the following technical solution:

[0007] A highly flexible polytetrafluoroethylene composite material comprises, by mass percentage, 1-20% of modified bentonite, 5-10% of coconut shell fiber, 5-10% of pineapple leaf fiber, 1-5% of graphene and polytetrafluoroethylene.

[0008] By adopting the above technical scheme, under the cooperation of coconut shell fiber, pineapple leaf fiber and graphene, coconut shell fiber and pineapple leaf fiber are interwoven to form a stable network skeleton with good elasticity, which not only increases the overall strength and flexibility of the composite material, but also makes the fiber more stable in the PTFE matrix and not easy to fall off. Graphene is dispersed in PTFE with a layered structure, and the network skeleton formed by the interweaving of coconut shell fiber and pineapple leaf fiber can be accommodated and fixed between its layers, forming a more closely combined and special system. At the same time, the layered structure of graphene can also effectively prevent the slippage and extraction of the fiber during the stress process, further improving the stability of the composite material.

[0009] During the subsequent high-temperature sintering process, the fluidity of the PTFE molecular chain is enhanced, which is conducive to its penetration and diffusion into the surface of coconut shell fiber, pineapple leaf fiber and graphene. This penetration and diffusion effect helps to form a tighter bonding interface and improve the overall strength of the composite material. At high temperatures, coconut shell fiber and pineapple leaf fiber may be partially carbonized to form carbonized fibers with higher hardness and strength. At the same time, graphene may also be graphitized to form a more stable graphite structure. The presence of these carbonized fibers and graphitized graphene can further improve the wear resistance of the composite material.

[0010] During the cooling process, the PTFE matrix shrinks. At this time, the graphene with holes provides space for PTFE to expand, avoiding the internal stress caused by shrinkage. At the same time, these holes can also act as tiny pores to reduce the rigidity of PTFE and increase its softness. The formation of these pores is closely related to the pore structure of graphene and the interwoven network of coconut shell fiber and pineapple leaf fiber.

[0011] Preferably, in terms of mass percentage, it includes 12% modified bentonite, 6% coconut shell fiber, 8.5% pineapple leaf fiber, 4% graphene, and 69.5% polytetrafluoroethylene.

[0012] By adopting the above technical solution, the dosage matching relationship between the raw materials is further limited, so as to give full play to the matching effect between the raw materials and improve the softness and wear resistance of the polytetrafluoroethylene composite material.

[0013] In a second aspect, the present application provides a method for preparing a highly flexible polytetrafluoroethylene composite material, using the following technical solution:

[0014] A method for preparing a highly flexible polytetrafluoroethylene composite material comprises the following steps:

[0015] Step 1: Prepare the mixture:

[0016] Step 1a: The silane coupling agent and ethanol are mixed until uniform to obtain a 1-5% soaking solution;

[0017] Step 1b: putting coconut shell fiber, pineapple leaf fiber and graphene into a soaking solution, and subjecting them to microwave treatment for 5-10 minutes at 100-150 W to obtain a microwave-treated product;

[0018] Step 1c: stirring the microwave-treated product at 2000-2500 r / min for 30-60 min to obtain a stirred product;

[0019] Step 1d: solid-liquid separation and drying to obtain a mixture;

[0020] Step 2: Alternately mix the mixture, modified bentonite, and polytetrafluoroethylene at high speed and low speed at a temperature of 20-30° C. to obtain an intermediate;

[0021] High speed is 960-1000r / min, 2-5s, low speed is 500-600r / min, 3-8s, high speed and low speed are alternated 3-6 times;

[0022] Step 3: Molding the intermediate under the condition of 25-50MPa, and the holding time is 3-5min;

[0023] Step 4: Sinter the molded intermediate at 220-370°C, and obtain a highly flexible polytetrafluoroethylene composite material after cooling.

[0024] Coconut shell fiber, pineapple leaf fiber and graphene are processed by combining special microwave and high-speed mixing methods. Coconut shell fiber, pineapple leaf fiber and graphene are evenly dispersed in advance, avoiding the situation where the raw materials are concentrated in one place and the performance improvement of the composite material is not synchronized.

[0025] During the process of mixing the treated mixture with polytetrafluoroethylene, a specific mixing method is adopted so that the mixture and modified bentonite can be evenly dispersed in the polytetrafluoroethylene, more fully cooperate with the polytetrafluoroethylene, and not easily form agglomerates. Subsequently, a special system can be quickly and smoothly formed in the polytetrafluoroethylene, not easy to fall off, and maintain a longer-lasting softness and wear-resistant effect.

[0026] Preferably, in step 2, the high speed is 980 r / min, 3 s, the low speed is 550 r / min, 5 s, and the high speed and low speed are alternately performed 4 times.

[0027] Preferably, in step 4, the temperature is raised from room temperature to 330°C for 5 hours, kept at 330°C for 0.5 hours, raised from 330°C to 370°C for 1 hour, kept at 370°C for 3 hours, lowered from 370°C to 220°C for 4 hours, and naturally cooled from 220°C to room temperature.

[0028] By adopting the above technical solution, the mixing conditions of step 2 and step 4 are further limited, so that the mixture can be fully dispersed and evenly matched. During sintering, the mixture can have a closer interface with polytetrafluoroethylene, improving the long-term wear resistance and softness. In the cooling process, the graphene with holes can provide expansion space, which is also conducive to enhancing the softness of the composite material.

[0029] Preferably, before soaking the coconut shell fiber and pineapple leaf fiber, the coconut shell fiber and pineapple leaf fiber are crushed to 1-10 μm.

[0030] Preferably, before crushing the coconut shell fiber and pineapple leaf fiber, the coconut shell fiber and pineapple leaf fiber are washed with water, and then dried to constant weight before crushing.

[0031] Preferably, the mass ratio of the total mass of the coconut shell fiber, pineapple leaf fiber and graphene to the soaking liquid is 1:(1-3).

[0032] In summary, this application has the following beneficial effects:

[0033] 1. The coconut shell fiber, pineapple leaf fiber and graphene work together to form a stable and elastic network structure, which significantly enhances the overall strength and softness of the composite material and makes the fiber more firmly in the PTFE matrix. Graphene is dispersed in PTFE in a layered form, which not only tightly fixes the network skeleton, but also effectively prevents the fiber from sliding and pulling out when it is stressed through its interlayer structure, thereby further improving the stability of the composite material.

[0034] 2. During the high-temperature sintering process, the fluidity of the PTFE molecular chain is improved, which promotes its more effective penetration into the surface of coconut shell fiber, pineapple leaf fiber and graphene, forming a tightly bonded interface and enhancing the overall strength of the composite material. In this process, coconut shell fiber, pineapple leaf fiber and graphene form a more stable structure. These changes improve the wear resistance of the composite material and further enhance its performance.

[0035] 3. During the cooling stage, the PTFE matrix will experience shrinkage. The pore structure of graphene and the pore structure of graphene and the interwoven network of coconut shell fiber and pineapple leaf fiber provide the necessary expansion space for PTFE, effectively alleviating the internal stress caused by shrinkage. In addition, these pores also play the role of micropores, reducing the rigidity of PTFE and giving it more softness. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a sample diagram of the highly flexible polytetrafluoroethylene composite material of Example 1 before compression performance testing.

[0037] Figure 2 This is a sample diagram of the high-softness polytetrafluoroethylene composite material of Example 1 before compression performance testing.

[0038] Figure 3 This is a diagram of the testing process of the bending performance of the high-flexibility polytetrafluoroethylene composite material of Example 1. From top to bottom, it corresponds to before the test, during the test, and after the test.

[0039] Figure 4 1 is a diagram showing the testing process of the bending performance of the high-softness polytetrafluoroethylene composite material of Example 1. From top to bottom, they correspond to before the test, during the test, and after the test. DETAILED DESCRIPTION

[0040] The present application is further described in detail below with reference to the accompanying drawings and embodiments.

[0041] All products used in the following examples and comparative examples are commercially available products.

[0042] Preparation Example 1

[0043] The preparation of modified bentonite comprises the following steps:

[0044] Step a: Sodium bentonite (purchased from Heishan County Everbright Bentonite Co., Ltd. in this preparation example, model SM-Y) was added into water to prepare a 10% suspension by mass, and the suspension was activated by stirring at room temperature for 30 minutes to fully disperse the sodium bentonite in water.

[0045] Step b: After heating the suspension to 80° C., add a nonionic polymeric fluorinated surfactant (the fluorinated surfactant S-386 produced by Asahi Glass Co., Ltd. in this preparation example) at a mass ratio of 8:100; react for 90 minutes and cool to room temperature.

[0046] Step c: Filter and remove water, and wash the filtered solid with deionized water for 3 times to remove the remaining surfactant.

[0047] Step d: The washed solid is dried at 105° C. and ground to obtain modified bentonite. Example 1

[0048] A highly flexible polytetrafluoroethylene composite material comprises 12% modified bentonite (preparation example 1), 6% coconut shell fiber, 8.5% pineapple leaf fiber, 4% graphene (Henan Wanying Refractory Material Technology Co., Ltd., model LG-1402), and 69.5% polytetrafluoroethylene.

[0049] The present application also provides a method for preparing a highly flexible polytetrafluoroethylene composite material, comprising the following steps:

[0050] Step 1: Prepare the mixture:

[0051] Step 1a: Add 3 kg of silane coupling agent (KH550) to 97 kg of 75% ethanol and stir to mix to obtain a 3% soaking solution.

[0052] Wash the coconut shell fiber and pineapple leaf fiber with clean water, dry them with hot air to constant weight, and then crush them into a size of 1-10μm.

[0053] Step 1b: according to the mass ratio of the total mass of coconut shell fiber, pineapple leaf fiber and graphene to the soaking liquid of 1:2, coconut shell fiber, pineapple leaf fiber and graphene are put into the soaking liquid, and microwave treatment is carried out at 120 W for 8 minutes to obtain a microwave-treated product.

[0054] Step 1c: The microwave-treated product is then stirred at a high speed of 2300 r / min for 45 min to obtain a stirred product.

[0055] Step 1d: Filter the stirred product to separate the solid and the liquid, wash the solid part with clean water, and then dry it with hot air to constant weight to obtain a mixture.

[0056] Step 2: The mixture, modified bentonite and polytetrafluoroethylene are mixed alternately at high speed and low speed at a temperature of 25° C. to obtain an intermediate.

[0057] The high speed is 980r / min, 3s, the low speed is 550r / min, 5s, and the high and low speeds are alternated 4 times.

[0058] Step 3: Add the intermediate into the molding machine and mold it at room temperature with a pressure of 40 MPa and a holding time of 4 minutes.

[0059] Step 4: Place the molded intermediate into a high-temperature furnace for sintering. The sintering process is controlled as follows: heating from room temperature to 330°C for 5 hours, keeping at 330°C for 0.5 hours, heating from 330°C to 370°C for 1 hour, keeping at 370°C for 3 hours, cooling from 370°C to 220°C for 4 hours, and naturally cooling from 220°C to room temperature. After cooling, a highly flexible polytetrafluoroethylene composite material is obtained. Example 2

[0060] A highly flexible polytetrafluoroethylene composite material, which is different from Example 1 in that it includes 20% modified bentonite (Preparation Example 1), 5% coconut shell fiber, 5% pineapple leaf fiber, 1% graphene (Henan Wanying Refractory Material Technology Co., Ltd., model LG-1402), and 69% polytetrafluoroethylene.

[0061] A method for preparing a highly flexible polytetrafluoroethylene composite material, which is different from that of Example 1, comprises the following steps:

[0062] Step 1: Prepare the mixture:

[0063] Step 1a: Add 1 kg of silane coupling agent (KH560) to 99 kg of 75% ethanol and stir to mix to obtain a 1% soaking solution.

[0064] Wash the coconut shell fiber and pineapple leaf fiber with clean water, dry them with hot air to constant weight, and then crush them into a size of 1-10μm.

[0065] Step 1b: according to the mass ratio of the total mass of coconut shell fiber, pineapple leaf fiber and graphene to the soaking liquid of 1:1, coconut shell fiber, pineapple leaf fiber and graphene are put into the soaking liquid, and microwave treatment is carried out at 100 W for 10 minutes to obtain a microwave-treated product.

[0066] Step 1c: The microwave-treated product is then stirred at a high speed of 2000 r / min for 60 min to obtain a stirred product.

[0067] Step 1d: Filter the stirred product to separate the solid and the liquid, wash the solid part with clean water, and then dry it with hot air to constant weight to obtain a mixture.

[0068] Step 2: The mixture, modified bentonite and polytetrafluoroethylene are mixed alternately at high speed and low speed at a temperature of 30° C. to obtain an intermediate.

[0069] The high speed is 960r / min, 5s, the low speed is 500r / min, 8s, and the high speed and low speed are alternated 3 times.

[0070] Step 3: Add the intermediate into the molding machine and mold it at room temperature with a pressure of 25 MPa and a holding time of 5 minutes.

[0071] Step 4: Place the molded intermediate into a high-temperature furnace for sintering. The sintering process is controlled as follows: heating from room temperature to 330°C for 5 hours, keeping at 330°C for 0.5 hours, heating from 330°C to 370°C for 1 hour, keeping at 370°C for 3 hours, cooling from 370°C to 220°C for 4 hours, and naturally cooling from 220°C to room temperature. After cooling, a highly flexible polytetrafluoroethylene composite material is obtained. Example 3

[0072] A highly flexible polytetrafluoroethylene composite material, which is different from Example 1 in that it includes 1% modified bentonite (Preparation Example 1), 10% coconut shell fiber, 10% pineapple leaf fiber, 5% graphene (Henan Wanying Refractory Material Technology Co., Ltd., model LG-1402), and 74% polytetrafluoroethylene.

[0073] A method for preparing a highly flexible polytetrafluoroethylene composite material, which is different from that of Example 1, comprises the following steps:

[0074] Step 1: Prepare the mixture:

[0075] Step 1a: Add 5 kg of silane coupling agent (KH550) to 95 kg of 75% ethanol and stir to mix to obtain a 5% soaking solution.

[0076] Wash the coconut shell fiber and pineapple leaf fiber with clean water, dry them with hot air to constant weight, and then crush them into a size of 1-10μm.

[0077] Step 1b: according to the mass ratio of the total mass of coconut shell fiber, pineapple leaf fiber and graphene to the soaking liquid of 1:3, coconut shell fiber, pineapple leaf fiber and graphene are put into the soaking liquid, and microwave treatment is carried out at 150 W for 5 minutes to obtain a microwave-treated product.

[0078] Step 1c: The microwave-treated product is then stirred at a high speed at 2500 r / min for 30 min to obtain a stirred product.

[0079] Step 1d: Filter the stirred product to separate the solid and the liquid, wash the solid part with clean water, and then dry it with hot air to constant weight to obtain a mixture.

[0080] Step 2: The mixture, modified bentonite and polytetrafluoroethylene are mixed alternately at high speed and low speed at a temperature of 30° C. to obtain an intermediate.

[0081] The high speed is 1000r / min, 2s, the low speed is 600r / min, 3s, and the high speed and low speed are alternated 6 times.

[0082] Step 3: Add the intermediate into the molding machine and mold it at room temperature with a pressure of 50 MPa and a holding time of 3 minutes.

[0083] Step 4: Place the molded intermediate into a high-temperature furnace for sintering. The sintering process is controlled as follows: heating from room temperature to 330°C for 5 hours, keeping at 330°C for 0.5 hours, heating from 330°C to 370°C for 1 hour, keeping at 370°C for 3 hours, cooling from 370°C to 220°C for 4 hours, and naturally cooling from 220°C to room temperature. After cooling, a highly flexible polytetrafluoroethylene composite material is obtained.

[0084] Comparative Example 1

[0085] A highly flexible polytetrafluoroethylene composite material, which is different from Example 1 in that coconut shell fiber is replaced by sisal fiber.

[0086] Comparative Example 2

[0087] A highly flexible polytetrafluoroethylene composite material, which is different from Example 1 in that pineapple leaf fibers are replaced by hydroxyethyl cellulose.

[0088] Comparative Example 3

[0089] A highly flexible polytetrafluoroethylene composite material, which is different from Example 1 in that graphene is replaced by carbon black.

[0090] Comparative Example 4

[0091] A method for preparing a highly flexible polytetrafluoroethylene composite material, which is different from Example 1 in that step 1b is carried out at 50 W, and step 1c is carried out at 500 r / min.

[0092] Comparative Example 5

[0093] A method for preparing a highly flexible polytetrafluoroethylene composite material, which is different from Example 1 in that step 1b is carried out at 300 W, and step 1c is carried out at 3000 r / min.

[0094] Comparative Example 6

[0095] A method for preparing a highly flexible polytetrafluoroethylene composite material, which is different from Example 1 in that step 2 is: stirring the mixture, modified bentonite, and polytetrafluoroethylene at a temperature of 10°C at a speed of 30 r / min for 5 minutes, and then stirring at a speed of 200 r / min for 10 minutes to obtain an intermediate.

[0096] 1. Softness test:

[0097] (1) The high-softness polytetrafluoroethylene composite materials of Examples 1-3 and Comparative Examples 1-6 were tested for compression properties with reference to GB / T 1041-2008, and the compression moduli were recorded in Table 1.

[0098] Some test pictures for reference Figure 1 , 2 .

[0099] (2) The bending properties of the high-softness polytetrafluoroethylene composite materials of Examples 1-3 and Comparative Examples 1-6 were tested with reference to GB / T 9341-2008, and the bending moduli were recorded in Table 1.

[0100] Some test pictures for reference Figure 3 , 4 .

[0101] 2. Wear resistance test: The high-softness polytetrafluoroethylene composite materials of Examples 1-3 and Comparative Examples 1-6 were tested with reference to GB / T 3960-2016, and the mass wear and volume wear were recorded in Table 1.

[0102] Table 1

[0103]

[0104] Comparative Examples 1-3 are based on Example 1, and any of the coconut shell fiber, pineapple leaf fiber, and graphene is replaced by other raw materials; Comparative Examples 4-5 are based on Example 1, and the processing conditions of coconut shell fiber, pineapple leaf fiber, and graphene in step 1b and step 1c are changed; Comparative Example 6 is based on Example 1, and the mixing conditions of the mixture, modified bentonite, and polytetrafluoroethylene in step 2 are changed.

[0105] According to the comparison of the test data in Table 1, the compression modulus and bending modulus of the composite materials of Examples 1-3 are lower than those of Comparative Examples 1-6, indicating that the composite materials of Examples 1-3 have better softness. The mass wear and volume wear of the composite materials of Examples 1-3 are significantly lower than those of Comparative Examples 1-6, indicating that the composite materials of Examples 1-3 have better wear resistance.

[0106] This indicates that destroying the special combination of coconut shell fiber, pineapple leaf fiber and graphene or changing the mixing conditions of the three or changing the mixing conditions of the mixture with polytetrafluoroethylene will make it impossible for coconut shell fiber, pineapple leaf fiber and graphene to fully play their special matching role in polytetrafluoroethylene, thereby affecting the formation of the special system and making it impossible to significantly improve the softness and wear resistance.

[0107] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A highly flexible polytetrafluoroethylene composite material, characterized in that: Based on the total mass of modified bentonite, coconut shell fiber, pineapple leaf fiber, graphene and polytetrafluoroethylene being 100%, the modified bentonite is 1-20%, the coconut shell fiber is 5-10%, the pineapple leaf fiber is 5-10%, and the graphene is 1-5%; The preparation method of the highly flexible polytetrafluoroethylene composite material comprises the following steps: Step 1: Prepare the mixture: Step 1a: The silane coupling agent and ethanol are mixed until uniform to obtain a 1-5wt% soaking solution; Step 1b: putting coconut shell fiber, pineapple leaf fiber and graphene into a soaking solution, and subjecting them to microwave treatment for 5-10 minutes at 100-150 W to obtain a microwave-treated product; Step 1c: stirring the microwave-treated product at 2000-2500 r / min for 30-60 min to obtain a stirred product; Step 1d: solid-liquid separation and drying to obtain a mixture; Step 2: Alternately mix the mixture, modified bentonite, and polytetrafluoroethylene at high speed and low speed at a temperature of 20-30° C. to obtain an intermediate; High speed is 960-1000r / min, 2-5s, low speed is 500-600r / min, 3-8s, high speed and low speed are alternated 3-6 times; Step 3: Molding the intermediate under the condition of 25-50MPa, and the holding time is 3-5min; Step 4: Sintering the molded intermediate at 220-370°C, and obtaining a highly flexible polytetrafluoroethylene composite material after cooling; The preparation of modified bentonite comprises the following steps: Step a: sodium bentonite is added into water to prepare a suspension with a mass percentage of 10%, and the suspension is activated by stirring at room temperature for 30 minutes to fully disperse the sodium bentonite in the water; Step b: After heating the suspension to 80° C., adding a nonionic polymeric fluorinated surfactant, wherein the mass ratio of the surfactant to the bentonite is 8:100; reacting for 90 minutes, and cooling to room temperature; Step c: filtering and removing water, and washing the filtered solid with deionized water for 3 times to remove the remaining surfactant; Step d: The washed solid is dried at 105° C. and ground to obtain modified bentonite.

2. The highly flexible polytetrafluoroethylene composite material according to claim 1, characterized in that: Based on the total mass of modified bentonite, coconut shell fiber, pineapple leaf fiber, graphene and polytetrafluoroethylene as 100%, the modified bentonite accounts for 12%, the coconut shell fiber accounts for 6%, the pineapple leaf fiber accounts for 8.5%, the graphene accounts for 4% and the polytetrafluoroethylene accounts for 69.5%.

3. A method for preparing a highly flexible polytetrafluoroethylene composite material according to any one of claims 1 to 2, characterized in that: The following steps are involved: Step 1: Prepare the mixture: Step 1a: The silane coupling agent and ethanol are mixed until uniform to obtain a 1-5wt% soaking solution; Step 1b: putting coconut shell fiber, pineapple leaf fiber and graphene into a soaking solution, and subjecting them to microwave treatment for 5-10 minutes at 100-150 W to obtain a microwave-treated product; Step 1c: stirring the microwave-treated product at 2000-2500 r / min for 30-60 min to obtain a stirred product; Step 1d: solid-liquid separation and drying to obtain a mixture; Step 2: Alternately mix the mixture, modified bentonite, and polytetrafluoroethylene at high speed and low speed at a temperature of 20-30° C. to obtain an intermediate; High speed is 960-1000r / min, 2-5s, low speed is 500-600r / min, 3-8s, high speed and low speed are alternated 3-6 times; Step 3: Molding the intermediate under the condition of 25-50MPa, and the holding time is 3-5min; Step 4: Sinter the molded intermediate at 220-370°C, and obtain a highly flexible polytetrafluoroethylene composite material after cooling.

4. The method for preparing a highly flexible polytetrafluoroethylene composite material according to claim 3, characterized in that: In step 2, the high speed is 980 r / min, 3 s, and the low speed is 550 r / min, 5 s, and the high and low speeds are alternately performed 4 times.

5. The method for preparing a highly flexible polytetrafluoroethylene composite material according to claim 3, characterized in that: In the step 4, the temperature is raised from room temperature to 330°C for 5 hours, kept at 330°C for 0.5 hours, raised from 330°C to 370°C for 1 hour, kept at 370°C for 3 hours, lowered from 370°C to 220°C for 4 hours, and naturally cooled from 220°C to room temperature.

6. The method for preparing a highly flexible polytetrafluoroethylene composite material according to claim 3, characterized in that: Before soaking the coconut shell fiber and pineapple leaf fiber, the coconut shell fiber and pineapple leaf fiber are crushed to 1-10 μm.

7. The method for preparing a highly flexible polytetrafluoroethylene composite material according to claim 6, characterized in that: Before crushing the coconut shell fiber and pineapple leaf fiber, the coconut shell fiber and pineapple leaf fiber are washed with water, and then dried to constant weight before crushing.

8. The method for preparing a highly flexible polytetrafluoroethylene composite material according to claim 3, characterized in that: The mass ratio of the total mass of the coconut shell fiber, the pineapple leaf fiber and the graphene to the soaking liquid is 1:(1-3).

Citation Information

Patent Citations

  • Preparation method of organic-bentonite-modified polytetrafluoroethylene (PTFE) oil seal material

    CN104558983A

  • Method for filling modification of waste polytetrafluoroethylene by using straw powder

    CN104927255A